TEXT AND METHODS OF LEARNING IT IN UZBEK LANGUAGE CLASSES (American Journal of Interdisciplinary Research and Development, 2022)
This article discusses the current tasks of the Uzbek language teaching methodology, which is organized on the basis of state educational standards. Information is provided on the wide variety of methods of working on the text in mother tongue education. In order to fill the identified gaps in students' knowledge, it is discussed about the wider implementation of the important and tested experience of writing the correct text of written works.